Analysis of household task allocation among selected couples in the Diliman area - Ravelo, James L. II; Trio, Consuelo Q. (2004.)
This study aims to determine the following: whether a couple's personal characteristics would have an influence on the number of hours they put in for household tasks, the degree of satisfaction derived from performing household tasks, and the reasons for performing those tasks. A survey research was dome where respondents were either interviewed about their allocation of household tasks or given survey forms to fill out. The respondents were couples living in and around of the U.P. Diliman campus vicinity, including the areas of Teacher's Village and Krus na Ligas. Once the necessary data was gathered, they were tabulated, charted, given statistical analysis, correlated and compared. The results displayed a typical trend across homes found in the Philippines and even abroad - males spent less time performing household tasks than the females. When it comes to age, the younger the couple was, the more time they would spend for household tasks. Income-wise, the more the couples earn, the less chance they would do household tasks themselves, instead choosing to hire househelp. Occupation primarily dictated the number of hours left to spend in performing household tasks. In general, both the males and females were satisfied as a result of performing household tasks, regardless of income and occupation. Meanwhile, majority of the males and females stated that they perform household tasks out of consideration of the partner who did not have time to perform those household tasks - again, regardless of their income and occupation. The study concludes on predictable notes. First was that females performed more household tasks than males ans spent more time doing so, and while age, monthly income and occupation gave certain trends, gender still had the greatest impact on household task allocation. Second was that couples are generally satisfied with performing household tasks, regardless of age, income, and occupation. Lastly, couples performed household tasks out of consideration of the others, because their partner was not in the house to perform household tasks as they were working outside the house. Practical applications of this research include helping spread gender awareness regarding tasks to help convince the others that household tasks aren't as unattractive and unreasonable as thought to be, and that household tasks can be performed by both genders and not exclusive to one. Another application is when a conflict between couples arise, the study could be of help not just for the couple, but also for professional help like a marriage counselor by examining whether the couples' personal characteristics may have had a hand in the origin and development of the conflict.
Thesis (BSHE) -- University of the Philippines Diliman.
Keywords: Household task; Couples